Functional Interaction Between the ESCRT‐I Component TSG101 and the HSV‐1 Tegument Ubiquitin Specific Protease. Issue 8 (August 2015) - Calistri, A.; Munegato, D.; Toffoletto, M.; Celestino, M.; Franchin, E.; Comin, A.; Sartori, E.; Salata, C.; Parolin, C.; Palù, G.
<x xml:space="preserve">Abstract</x> Similar to phosphorylation, transient conjugation of ubiquitin to target proteins (ubiquitination) mediated by the concerted action of ubiquitin ligases and de‐ubiquitinating enzymes (DUBs) can affect substrate function. As obligate intracellular parasites, viruses rely on different cellular pathways for their own replication and the well conserved ubiquitin conjugating/de‐conjugating system is not an exception. Viruses not only usurp the host proteins involved in the ubiquitination/de‐ubiquitination process, but they also encode their own ubiquitin ligases and DUBs. Here we report that an N‐terminal variant of the herpes simplex virus (HSV) type‐1 large tegument protein VP1/2 (VP1/21–767), encompassing an active DUB domain (herpesvirus tegument ubiquitin specific protease, htUSP), and TSG101, a component of the endosomal sorting complex required for transport (ESCRT)‐I, functionally interact. In particular, VP1/21–767 modulates TSG101 ubiquitination and influences its intracellular distribution. Given the role played by the ESCRT machinery in crucial steps of both cellular pathways and viral life cycle, the identification of TSG101 as a cellular target for the HSV‐1 specific de‐ubiquitinating enzyme contributes to the clarification of the still under debate function of viral encoded DUBs highly conserved throughout the Herpesviridae family. J. Cell. Physiol. 230: 1794–1806, 2015. © 2014 Wiley Periodicals, Inc.